Nata Cellulose Production Development as A Health Product from Coconut Wastewater Using Acetobacter xylinum Bacterium - Mandey, Lucia C.; Kandou, Jenny E. A.; Langi, Tineke M. (Jurnal Ilmu dan Teknologi Pangan, 2016)
The objective of the study was to develop the cellulose Nata/dietary fiber production from coconut water using bacterium, Acetobacter xylinum, as health product containing natural fibers. The study used Complete Randomized Design with treatments of different concentration of inoculum Acetobacter xylinum, each of which had 3 replications. The treatments were liquid inoculum of Acetobacter xylinum: A = 5 %/1000 ml (5 % of liquid inocula were added into 1000 ml of coconut water), B = 7.5 %/1000 ml (7.5 % of liquid inocula were added into 1000 ml of coconut water), C = 10 %/1000 ml (10 % of liquid inocula were added into 1000 ml of coconut water), D = 12.5 %/1000 ml (12.5 % of liquid inocula were added into 1000 ml of coconut water), and E = 15 %/1000 ml (15 % of liquid inocula were added into 1000 ml of coconut water). This study concluded that 1) the liquid inocula of Acetobacter xylinum could result in cellulose nata; 2) the highest quality of the cellulose nata/dietary fiber from the use of liquid inocula of Acetobacter xylinum) was found in treatment E for pellicle weight, 1009.3 gr, layer thickness, 1.50 cm, rendement, 90.82 %, and water content, 79.71 %, and fiber level, 1.31 %, for treatment D and E, respectively. Keywords: cellulose nata, coconut wastewater, Acetobacter xylinum bacterium